Articulación de los modos de producción y los dos circuitos de la economía urbana: los mayoristas de Lima, Perú: Autor: Milton Santos (+) - Santos, Milton (2021)
The author devoted his main attention to economic issues within cities and the socio-spatial relationships they have with their region, country and the world. In the case of Peru, he studies a particular case of Lima and the wholesale food market (La Parada) of this city. These micro-scale studies are very precise about the commercialization of fresh food and the relationship between wholesalers and retailers, transporters, producers and intermediaries, as well as those who offer services and complementary activities within the value chain of agri-food products that They come from the various agricultural areas of the interior of Peru to Lima.